Morphological and Molecular detection of some Opportunistic Free- living Amoebae Isolated From Environmental and clinical Sources in Thi- Qar province / Iraq - AL-Aboody, Bassad; Altooma , Muslim; Al-Badran , Adnan; Alashkham, Fatma (University of Thi-Qar Journal of Science, 2024)
Free- living amoebae (FLA) are predatory heterotrophic protozoa that are widely distributed in various environmental sources .They are known to cause serious human infections including a fatal encephalitis, pneumonia and a blinding keratitis. was performed in Thi –Qar province south of Iraq in order to detection of the opportunistic FLA and identified by morphological characters in the culture , Polymers Chain Reaction (PCR) amplification a targeting specific genes for each genus During the period from February to September 2020, one hundred and two (102)samples were collected including 75samples from different environmental sources, soil , water ( rivers , tap water , tank water, stagnant water, the marshes water and drops of water from the air conditioner units ) and animals wastes(lizard , birds and wild mice) ,and 27 clinical samples ( eye, skin, ear, and Cerebral Spinal Fluid)collected from Al-Hussain teaching hospital , Bint AL-Huda teaching hospital , Al-Hboobi teaching hospital and private laboratories in Thi-Qar province . All samples were cultured in the Non Nutrient agar medium (NN-agar medium) and then examined by light microscope and recognized morphologically the trophozoites and cysts of opportunistic amoebas that belong to the genera ; Naegleria fowleri, Acanthamoeba spp.(A. triangularis ,A. astronyxis ,A. castellini A. polyphaga ), Sappinia spp.(S. pedata , S. diploidea) and Balamuthia mandrillaris, the study found 62 (60.78%) samples were positive for total opportunistic FLA, and 40(39.21%) samples were negative, the incidence of FLA in environmental samples were 76% and in clinical samples were18.51 % .